Determinação da duração do período de molhamento foliar em cultivos de batata - Streck, Luciano (2006)
The beginning of wetness and the end of leaf drying in potato crop was determined aiming to compare observed values of wetness duration with values estimated from meteorological data and from mathematical models. Three growing seasons with potato were performed at the experimental area of the Crop Science Department of the Federal University of Santa Maria, from 05/03 to 07/06/2004, from 23/07 to 20/10/2004, and from 10/03 to 09/06/2005. Plants were grown at a 0.3x0.8 m spacing. The duration of the leaf wetness was observed visually in the 2004 growing seasons and with six electronic wetness sensors in the 2005 growing season. Meteorological data were measured in an automated weather station installed at 1.5 m above the canopy and a datalogger with psycrometric sensors installed within the canopy (0.1 m height), and above it at 0.4 m, 1.0 m and 1.5 m heights in 2004 and at 0.5 m and 1.5 m heights in 2005. Net radiation was also measured above the canopy. For estimating the duration of the wetness period, the relative humidity thresholds of ≥80%, ≥85%, ≥87%, ≥90%, and ≥87% with an extension up to values of 70% relative humidity. This extension for relative humidity to values of 70%, considered that the beginning of leaf wetness was assumed when a minimum increase of 3% in relative humidity occurred in the 70% and 87% range, during half an hour, and the end of drying was assumed when a decrease of relative humidity greater than 2% occurred in half an hour in the range of 87% and 70% relative humidity. In addition, estimates from the difference of temperature and dew point temperature, and vapor pressure deficit at different heights were performed after defining the thresholds for the moments of beginning of wetness and end of leaf drying. Estimates were also performed with CART model, leaf energy budget model, and Penman model. Visual observations showed that, regardless of the time of the year, wetness and drying of leaves lasts about 1h15min and 3h at evening and dawn, respectively, when conditions are favorable to both processes. It was verified that the duration of leaf wetness can be estimated using the 87% relative humidity threshold with an extension down to 70% measured in the canopy at 1.5 m height. It was also verified that the 90% relative humidity threshold above canopy is not appropriated to estimate the dew wetness period, but this threshold can be used when is measured at 0.1 m within the canopy and so is the 87% relative humidity threshold. CART model with correction of wind speed to the top canopy can be used to estimate the wetness period, with equivalent results to the relative humidity at 1.5 m height approach. The leaf energy budget model is the most appropriated for estimating dew wetness period in a potato canopy, even though this model needs additional calculation and meteorological variables compared to others models.